1984
DOI: 10.1099/00221287-130-3-557
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cellular Efflux by a Galactosamine Polymer from Neurospora crassa

Abstract: A cationic polymer of D-galactosamine was isolated from culture filtrates of a colonial temperature-sensitive strain of Neurospora crassa. Adsorption of the polymer to the cell surface initiated immediate efflux of low molecular weight metabolites and subsequent loss of viability. The polymer appeared to bind to those sites on the cell surface that normally bind calcium ions. Chemical analysis of the polymer showed it to be partially N-acetylated. The polymer had an isoelectric point of 8.4. Thirty percent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The degree of deacetylation of A. fumigatus GAG is not known, however, analysis of the GAG from Neurospora crassa found that the polymer has between 30 and 70% deacetylated galactosamine depending on the growth conditions. In N. crassa, deacetylation was correlated with the level of expression of a deacetylase [39][40][41] . Recently, it was shown that Aspergillus oryzae produces GAG with a degree of deacetylation near 50% 42 .…”
Section: Agd3 Contains a Unique Carbohydrate Binding Module (Cbm)mentioning
confidence: 99%
“…The degree of deacetylation of A. fumigatus GAG is not known, however, analysis of the GAG from Neurospora crassa found that the polymer has between 30 and 70% deacetylated galactosamine depending on the growth conditions. In N. crassa, deacetylation was correlated with the level of expression of a deacetylase [39][40][41] . Recently, it was shown that Aspergillus oryzae produces GAG with a degree of deacetylation near 50% 42 .…”
Section: Agd3 Contains a Unique Carbohydrate Binding Module (Cbm)mentioning
confidence: 99%